Organizational Conflict Management Model in the Development of Islamic Educational Institutions - Romat Efendi Sipahutar; Devi Syukri Azhari (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2026)
This study aims to analyze and formulate an organizational conflict management model tailored to the development of Islamic educational institutions. Employing a qualitative field research design conducted over a period of eight months (March–October 2024), data were collected through in-depth interviews with 18 participants (comprising 4 institutional leaders, 8 educators, and 6 administrative staff), participant observation, and documentation. The study site was selected purposively, with data analyzed using Miles and Huberman’s interactive model and validated through source, technique, and time triangulation. The findings reveal that organizational conflicts primarily originate from perceptual discrepancies, ineffective communication, inequitable task distribution, and non-adaptive leadership styles. Conflict management is systematically executed through identification, factual clarification (tabayyun), deliberative consultation (musyawarah), leadership mediation, joint decision-making, and continuous evaluation. Crucially, these processes are deeply anchored in Islamic ethical principles, including justice, brotherhood (ukhuwah), and reconciliation (ishlah). The research successfully develops a collaborative-participatory conflict management model that actively involves all stakeholders in crafting win-win solutions while preserving moral and spiritual integrity. The study concludes that integrating modern managerial frameworks with Islamic values significantly enhances organizational harmony, elevates institutional performance, and fosters sustainable development in Islamic educational settings. Consequently, implementing a structured, value-based conflict management system is imperative for institutional leaders to effectively navigate organizational dynamics, transform potential friction into constructive innovation, and continuously improve educational quality in contemporary contexts.